Preserving cultural heritage and empowering indigenous communities for sustainable development in Fiji - Mumtaz Alam (Social Sciences and Humanities Open)
This study examines how Indigenous Fijians reconcile cultural preservation with progress in political and economic domains to attain sustainable development within Fiji's distinct cultural framework. This research analyzes solutions utilized by Indigenous people to preserve their traditions while addressing modern difficulties, based on scholarly research, government papers, international agency publications, and NGO records.Indigenous Fijians have acted as stewards of their nation's extensive cultural legacy for millennia. Nevertheless, contemporary forces such as globalization, urbanization, environmental deterioration, and social transformation pose tremendous dangers to ancient practices. This study assesses the efficacy of existing initiatives and regulations aimed at safeguarding Indigenous Fijian culture, pinpointing essential areas for urgent intervention.The study examines the complex interplay between cultural preservation and sustainable development, illustrating that the empowerment of Indigenous communities, via improved educational opportunities, economic prospects, and significant involvement in decision-making, is directly linked to holistic development outcomes. This research evaluates the effects of government policies, international alliances, and grassroots activities on the social and economic well-being of Indigenous communities. Results: indicate both achievements and constraints of current preservation initiatives, offering significant insights for forthcoming policy formulation. This research enhances academic debate on cultural preservation, civic participation, and inclusive development within Pacific Island contexts, highlighting the role of past knowledge in shaping modern advancement.The report promotes a comprehensive approach that acknowledges cultural heritage as essential to the sustainable development goals of Indigenous communities. This paradigm fosters success, adaptability, and equity while guaranteeing that traditional knowledge systems are vital to Fiji's growth trajectory, ultimately illustrating that cultural preservation and modernization can coexist synergistically.